COVID-19: The Impact on Internal Medicine Resident Training - Odalys Estefania Lara Garcia (Avicenna Journal of Medicine, 2022)
The novel coronavirus disease 2019 (COVID-19) pandemic has impacted the lives of physicians at all levels. The workloads and working hours have increased tremendously which affected the time spent on administrative and academic duties. The COVID-19 pandemic imposed a lot of challenges on academic institutions in term of providing quality of care to patients and maintaining the quality of education for trainee. Herein, we discuss the challenges and impact of the pandemic on residents training.